Na2B11H13 and Na11(B11H14)3(B11H13)4 as potential solid-state electrolytes for Na-ion batteries - Souza, Diego H.P.; D'Angelo, A.M.; Humphries, Terry D.; Buckley, Craig E.; Paskevicius, Mark (ROYAL SOC CHEMISTRY, 2022)
Solid-state sodium batteries have attracted great attention owing to their improved safety, high energy density, large abundance and low cost of sodium compared to the current Li-ion batteries. Sodium-boranes have been studied as potential solid-state electrolytes and the search for new materials is necessary for future battery applications. Here, a facile and cost-effective solution-based synthesis of Na2B11H13 and Na11(B11H14)3(B11H13)4 is demonstrated. Na2B11H13 presents an ionic conductivity in the order of 10−7 S cm−1 at 30 °C, but undergoes an order-disorder phase transition and reaches 10−3 S cm−1 at 100 °C, close to that of liquids and the solid-state electrolyte Na-β-Al2O3. The formation of a mixed-anion solid-solution, Na11(B11H14)3(B11H13)4, partially stabilises the high temperature structural polymorph observed for Na2B11H13 at room temperature and it exhibits Na+ conductivity higher than its constituents (4.7 × 10−5 S cm−1 at 30 °C). Na2B11H13 and Na11(B11H14)3(B11H13)4 exhibit an oxidative stability limit of 2.1 V vs. Na+/Na.